Structure–property relations in semi‐crystalline combinatorial poly(urethane‐isocyanurate)‐type hydrogels. Issue 9 (10th June 2022) - Driest, Piet J; Dijkstra, Dirk J; Stamatialis, Dimitrios; Grijpma, Dirk W
Abstract: Within the fields of regenerative medicine and tissue engineering, the development of tough hydrogel biomaterials is a challenging topic that has received much attention over the past few years. Recently, a method was developed to synthesize tough combinatorial poly(urethane‐isocyanurate) (PUI)‐type hydrogels by the trimerization of mixtures of NCO‐functionalized prepolymers. As this synthesis approach allows a large degree of freedom in terms of polymer network design with a high level of control over the polymer network structure, the resulting systems are ideally suited for studying structure–property relations in tough hydrogel systems. In this work, we aim to systematically investigate the influence of introducing a hydrophobic component into a PUI polymer network on the mechanical properties of the resulting PUI hydrogels. Additionally, the effect of (the degree of) crystallinity of the hydrophobic network component is investigated. For this, two series of combinatorial PUI hydrogels are synthesized, based on a hydrophilic poly(ethylene glycol) prepolymer and increasing amounts of either a crystallizable hydrophobic prepolymer (poly( ε ‐caprolactone)) or an amorphous hydrophobic prepolymer (poly(propylene glycol)). It is shown that the toughness of amorphous PUI hydrogels is hardly influenced by the hydrophobic content, whereas the toughness of semi‐crystalline PUI hydrogels strongly increases with increasing hydrophobic content. Also, the toughness of the latter hydrogels increases further with increasing degree of crystallinity of the hydrogel. Finally, it is shown that the semi‐crystalline PUI hydrogels are promising materials for biomedical adhesive and coating applications, as well as for load‐bearing biomedical applications within the fields of tissue engineering and regenerative medicine. © 2022 Covestro Deutschland AG. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Industrial Chemistry. Abstract : By systematically varying the crystallizable hydrophobic content in combinatorial poly(urethane‐isocyanurate)‐type hydrogels, a strong correlation is shown between the toughness and crystallinity of these hydrogels in the hydrated state.